Does the Hartz IV Reform have an Effect on Matching Efficiency in Germany? A Stochastic Frontier Approach - Katja Hillmann (Verein für Socialpolitik, 2010)
In the course of a comprehensive labor market reform started in 2003 and finished through the implementation of the most radical measure Hartz IV in 2005, I exploit its impact on matching processes in Germany. I use disaggregated data for 178 local employment agencies to examine the effects of stocks and flows of vacancies and unemployed on the hiring rate as well as on the matching efficiency. Building on the work of Ibourk et al. (2004) and Fahr and Sunde (2006), I employ a stochastic frontier analysis. As a functional framework I choose the translog function to address the interactions of stocks and flows in generating new hires. Furthermore, the twofold structure of a stochastic frontier allows for a modeling of potential sources (e.g. Hartz IV) expected to induce an increased or decreased matching efficiency. My results suggest that Hartz IV exhibits a significantly positive impact on the hiring rate and the matching efficiency. Compared to 1998, on average matching efficiency experienced an increase in 2007.
Keywords: C23; J64; J68; 330; Labor Market Reform; Matching Models; Stochastic Frontier Analysis; German